An Experimental Study on Mahehwar Dhoop to Evaluate Fumigation Effect in Comparison with Bacillocid - Renu Rathi1 , Bharat J. Rathi2 , Roshna Bhutada3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Ayurveda advocates fumigation as a method of sterilization and therapeutic tool for differentinfective diseases and mental disorders. However, it is not popular and proven scientifically hence there isgreat scope and prospects for research. For patient safety, fumigation is a regular protocol.Aim and Objectives: It is the need of the hour to search a safe, cheap, effective and easily available drugsfor fumigation hence Maheshwar Dhoop-MD was chosen and compared its efficacy with control- Bacillocid.Material and Method: Study was performed in Shalakya (eye-ENT), Panchkarma procedure rooms andminor operation theatre by pre-post swab and Agar plate exposure on 2nd (MD) and 4th week (Bacillocid)monthly once each for total three months. The microbial load was estimated for different micro-organismslike bacteria, fungus etc and subjected to statistical analysis.Observation and Results: The study revealed that the effect of Dhoopana was significant in comparisonwith Bacillocidto control both during study period and follow up period up to 6 days against bacterias andfungus. Conclusion: It was found that MD is safe, cheap and equally efficient as Bacillocid (p<0.0001) withone-week residual effect.